Taxonomic Studies on Australian Psammoecus Latreille (Coleoptera, Silvanidae, Brontinae) - Karner, Michael (European Journal of Taxonomy, 2020)
Two new species of Psammoecus Latreille, 1829 from Australia are described: Psammoecus australis sp. nov. and P. venustus sp. nov. A taxonomic revision and diagnoses for other Australian species are provided. Psammoecus obesus Grouvelle, 1919 is recorded from Australia for the first time. Two new synonyms are discovered: Psammoecus t-notatus Blackburn, 1908 = P. amoenus Grouvelle, 1912 syn. nov.; Psammoecus vittifer Blackburn, 1903 = P. concolor Grouvelle, 1919 syn. nov. A lectotype is designated for Psammoecus concolor Grouvelle, 1919.